2011
DOI: 10.21608/jpp.2011.85627
|View full text |Cite
|
Sign up to set email alerts
|

Using Different Sources of Compost Tea on Grapes

Abstract: The present investigation was carried out during 3 successive seasons from 2008 to 2010. The work in the first year was considered as a preliminary trial. This investigation was conducted on 14-year-old King Ruby grapevines cultivar growing at a private vineyard called Chycheny located at meniet samanood village near Mansoura city, Dakahlia Governorate, Egypt. The study aimed to evaluate the effect of different sources of compost tea with or without citric acid on vegetative growth, leaf mineral content, physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…The present results are in the same trend with those mentioned by (Gawad Shaheen et al, 2012) on Crimson seedless grapevines and (El-Boray et al, 2013) on King Ruby who worked on humic acid, (Sabry et al, 2009) on Red Globe, (Abd El-Hameed et al, 2010) on Thompson seedless and (Abd El-Aal et al, 2013) on Superior grapevines who worked on (EM), (Fayed, 2010a) on Thompson seedless and (Mostafa et al, 2011) on King Ruby who worked on ascorbic acid and citric acid. They confirmed that the soil application of humic acid and (EM) and spraying application of ascorbic and citric acid enhanced the absorption of macro-elements as they gave the highest values of N, P and K in leaf petioles as compared with that of control.…”
Section: N P and K Content In Leaf Petiolessupporting
confidence: 89%
See 2 more Smart Citations
“…The present results are in the same trend with those mentioned by (Gawad Shaheen et al, 2012) on Crimson seedless grapevines and (El-Boray et al, 2013) on King Ruby who worked on humic acid, (Sabry et al, 2009) on Red Globe, (Abd El-Hameed et al, 2010) on Thompson seedless and (Abd El-Aal et al, 2013) on Superior grapevines who worked on (EM), (Fayed, 2010a) on Thompson seedless and (Mostafa et al, 2011) on King Ruby who worked on ascorbic acid and citric acid. They confirmed that the soil application of humic acid and (EM) and spraying application of ascorbic and citric acid enhanced the absorption of macro-elements as they gave the highest values of N, P and K in leaf petioles as compared with that of control.…”
Section: N P and K Content In Leaf Petiolessupporting
confidence: 89%
“…In addition, (Sabry et al, 2009) on Red Globe, (Abd El-Hameed et al, 2010 andAhmed et al, 2011) on Thompson seedless and (Abd El-Aal et al, 2013) on Superior grapevines, they found that vegetative growth parameters were significantly increased by (EM) applied. Also, (Fayed, 2010a) on Thompson seedless, (Mostafa et al, 2011) on King Ruby and (Nerway, 2011) on Rash-Mew grape, they found that spraying ascorbic acid and citric acid increased shoot length, leaf area and total chlorophyll in leaves.…”
Section: Shoot Length Leaf Area and Leaf Chlorophyll Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil application of compost tea gave better effect on fruit yield of pear trees compared to control (Mohamed et al, 2010). Also, Mostafa et al (2011) reported that compost tea produced the maximum yield of grapes. Biofertilizers are the most important for plant production and soil as they play an important role in improving fruit quality and yield of grapevines (Akl et al, 1997).…”
Section: Fruits Number and Total Yieldmentioning
confidence: 99%
“…Soil application of compost tea gave better effect on macro and micro elements of pear trees (Mohamed et al, 2010). Also, Mostafa et al (2011) reported that compost tea improvement of the nutritional status of grapes. Additionally, the great availability and release of N, P and K due to the application of biofertilizers were announced by Abd-Rabou ( 2006) on avocados and mangos.…”
Section: Leaf Mineral Contentmentioning
confidence: 99%